Pengaruh Ekstrak Etanol Kulit Batang Duwet (Syzygium cumini L.) terhadap Pertumbuhan Staphylococcus aureus - Fitria, Faizatul; Untarto Swandono, Hari; Agusti Lukis, Prima; Werdiningsih, Wiwik (Fakultas Sains, Teknologi, dan Analsisi Institut ilmu Kesehatan Bhakti Wiyata, 2025)
Bacterial infections, especially those caused by Staphylococcus aureus, are a serious global health problem. This bacterium can cause a range of diseases, from mild skin infections to potentially fatal sepsis. It has also been reported to have developed resistance to antibiotics, which highlights the need for developing natural antibiotics with minimal side effects. The Duwet plant (Syzygium cumini L.), particularly its bark, is traditionally used to treat dysentery, diarrhea, and dyspepsia, and contains numerous bioactive compounds. Due to these benefits and its compounds, the bark of the duwet tree has the potential to possess beneficial antibacterial properties. The purpose of this study was to determine the extent to which the ethanol extract of duwet bark can inhibit the growth of Staphylococcus aureus in a laboratory setting (in vitro). The methods used included an extraction process where the duwet bark was soaked in 96% ethanol, followed by a phytochemical test to determine its chemical content. The extract was then tested for its ability to inhibit the growth of Staphylococcus aureus using the well diffusion method at concentrations of 20%, 40%, and 60%. The results showed that the duwet bark extract had the strongest antibacterial activity at a concentration of 60%, with an inhibition zone of 10.67 ± 2.25 mm, which falls into the moderate category.